2017
DOI: 10.1111/jgs.14791
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss and Risk of Dementia in the Community: the Hisayama Study

Abstract: OBJECTIVES:To clarify the effect of tooth loss on development of all-cause dementia and its subtypes in an elderly Japanese population. DESIGN: Prospective cohort study. SETTING: The Hisayama Study, Japan. PARTICIPANTS: Community-dwelling Japanese adults without dementia aged 60 and older (N = 1,566) were followed for 5 years (2007)(2008)(2009)(2010)(2011)(2012). MEASUREMENTS: Participants were classified into four categories according to baseline number of remaining teeth (≥20, 10-19, 1-9, 0). The risk estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
140
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(143 citation statements)
references
References 43 publications
(102 reference statements)
2
140
0
1
Order By: Relevance
“…1,2 Although the implant treatment modality has demonstrated a considerably high success rate for decades, various biological, mechanical, and technical complications have been reported consistently and both the incidence and prevalence have also steadily increased. Conversely, in a 5-15 year follow-up study, Ragnert et al 9 reported a fracture rate of 6% in the maxilla, and 3% in the mandible, whereas Takeshita et al 10 also reported a relatively high fracture rate of 5 fractures in 68 (7.4%) implants. 4,5 Balshi et al 6 reported that fractures occurred in only 8 out of 4045 (0.2%) implants, whereas Mericske-Stern et al 7 reported a fracture rate of 1 out of 66 (1.5%) implants, and Zarb et al 8 reported no fractures among 274 implants.…”
Section: Introductionmentioning
confidence: 95%
“…1,2 Although the implant treatment modality has demonstrated a considerably high success rate for decades, various biological, mechanical, and technical complications have been reported consistently and both the incidence and prevalence have also steadily increased. Conversely, in a 5-15 year follow-up study, Ragnert et al 9 reported a fracture rate of 6% in the maxilla, and 3% in the mandible, whereas Takeshita et al 10 also reported a relatively high fracture rate of 5 fractures in 68 (7.4%) implants. 4,5 Balshi et al 6 reported that fractures occurred in only 8 out of 4045 (0.2%) implants, whereas Mericske-Stern et al 7 reported a fracture rate of 1 out of 66 (1.5%) implants, and Zarb et al 8 reported no fractures among 274 implants.…”
Section: Introductionmentioning
confidence: 95%
“…Cognitive impairment and its neuropathological manifestations, such as Alzheimer's disease and dementia in an ageing population, place significant burdens on health systems . Many studies have proposed that poor oral health, specifically periodontal disease and tooth loss, is an important risk factor for cognitive impairment and increases the risk of dementia . Conversely, some studies also suggested that people with poor cognitive function or dementia might have poorer oral hygiene and experience more dental caries, periodontal disease and more tooth loss than those with normal cognition .…”
Section: Introductionmentioning
confidence: 99%
“…Study has shown that women are more affected by dental losses than men (Takeuchi et al, 2017). In our study, 56.4% of the elderly were edentulous, with greater odds for women (1.5; p=0.009) to be affected by edentulism (p=0.009).…”
Section: Discussionmentioning
confidence: 42%